2010
DOI: 10.1016/j.tsf.2010.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Realization of an extremely low reflectance surface based on InP porous nanostructures for application to photoelectrochemical solar cells

Abstract: Extremely low reflectance was obtained from InP porous nanostructures in UV, visible, and near-infrared ranges. Porous samples were electrochemically prepared on which 130-nm-diameter nanopores were formed in a straight, vertical direction and were laterally separated by 50-nm-thick InP nanowalls. The reflectance strongly depended on the surface morphology. The lowest reflectance of 0.1% in the visible light range was obtained after the irregular top layer had been completely removed. Superior photoelectrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…This phenomenon is very similar to the case of InP porous nanostructures. 19 In samples C and B , pores with enlarged openings appeared on the surface, where air holes are closely aligned between the thin GaN walls. This kind of Figure 8 Photoelectrochemical characteristics of non-porous and porous GaN: sample A formed at t a = 300 s, sample B formed at t a = 600 s, sample C formed at t a = 1800 s, and sample B formed at t a = 600 s after H 3 PO 4 treatment.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This phenomenon is very similar to the case of InP porous nanostructures. 19 In samples C and B , pores with enlarged openings appeared on the surface, where air holes are closely aligned between the thin GaN walls. This kind of Figure 8 Photoelectrochemical characteristics of non-porous and porous GaN: sample A formed at t a = 300 s, sample B formed at t a = 600 s, sample C formed at t a = 1800 s, and sample B formed at t a = 600 s after H 3 PO 4 treatment.…”
Section: Resultsmentioning
confidence: 94%
“…The most well-known application of an electrochemical process is the formation of porous nanostructure by anodic etching in which a high-density array of nanometer-or micrometer-sized pores is formed with high productivity over a large area on the semiconductor surface. 17 We have recently reported that InP porous nanostructures showed low photoreflectance and high photoabsorption, 18,19 which are very promising features for porous nanostructures used in the photoelectric conversion devices such as photodetectors and solar cells. Besides, the electrochemical process is applicable to various semiconductors, [20][21][22][23][24] even chemically stable materials such as GaN, [25][26][27][28][29] without causing processing damage.…”
mentioning
confidence: 99%
“…5,6 In addition, this technique is performed at room temperature and does not require any complicated process such as lithography, indicating lower damage and higher productivity than other nanostructure fabrication techniques such as reactive ion etching and selective-area growth.…”
mentioning
confidence: 99%
“…[1][2][3][4] Among the various techniques for improving their conversion efficiency, porosification utilizing EC reactions is one of the most powerful because a high-density array of pores exhibits high specific surface area, low reflectance, and high absorptance properties. 5,6 In addition, this technique is performed at room temperature and does not require any complicated process such as lithography, indicating lower damage and higher productivity than other nanostructure fabrication techniques such as reactive ion etching and selective-area growth. [7][8][9][10] Many reports involving porosification use photo-assisted EC etching utilizing charge carriers generated by band-edge absorption.…”
mentioning
confidence: 99%
“…Electrochemically formed porous structures, which have been applied for various materials, [4][5][6][7] are promising nanostructures for the above-mentioned applications. Many researchers have reported the electrochemical formation of GaN-porous structures.…”
mentioning
confidence: 99%